THE ANALYSIS OF DIGITAL MARKETING IN EFFORTS TO IMPROVE COMPETITIVE ADVANTAGES IN MSMEs - Winaika Irawati; Rohmad Prio Santoso (Universitas Islam Lamongan, 2023)
The purpose of the research is to find out, 1) the effect of implementing digital marketing through interactive indicators on competitive advantage, 2) the effect of implementing digital marketing through incentive program indicators on competitive advantage, 3) the effect of implementing digital marketing through site design indicators on competitive advantage. 4) the effect of applying digital marketing through cost/transaction indicators on competitive advantage This research is a quantitative research, which uses multiple linear regression analysis as its approach. The research population is culinary business actors in the sugarcane area of ??Sokosari. The research sample was 30 respondents. The research findings show: digital marketing indicators, namely interactive, incentive programs, site design, cost/transactions have partial or simultaneous effects on competitive advantage in the culinary business of the Sokosari area. seen from the simultaneous test where sig 0.00 <0.05